WOMAN: THE CATALYST FOR SOCIAL EDUCATION AND LOCAL WISDOM OF SAKAI COMMUNITY IN RIAU - Erni, Sukma; Roza, Ellya; Yasnel, Yasnel; Johanda, Johanda; Kalipke, Mohamad Agar; Miski, Cut Raudhatul; Husin, Norhazlina (Al-Qalam, 2024)
This research concerns with the effort of the Sakai tribe in maintaining their local wisdom and social characters from generation to the next generation eventhough there is minimum outside social interaction. This research involved 9 key informants spread across 5 villages in Bengkalis Regency. They explained their lives in the Sakai people's village, how they modeled and educated the generations and communities to build a safe and peaceful life. The research findings confirm that in their daily lives, women interact a lot with children and other fellow women around the house. The socially visible modeling of women's behavior becomes an imitative model by their community. Patience, thoughtfulness, saving, restraint, not talkative, not getting angry often, using the mantra of overcoming minor problems, including demonstrating how they should behave into a social education slowly builds generational character and teach them how to survive in even difficult situations. This research concludes that Sakai women with their diversity have a strong role as a catalyst for social education and local wisdom of the Sakai people